RADIKALISME ISLAM DAN PERADILAN: Pola-pola Intervensi Kekuasaan dalam Kasus Komando Jihad di Indonesia - Khudzaifah Dimyati; Mohammad BusjroMuqoddas; Kelik Wardiono (Faculty of Law, Universitas Jenderal Soedirman, 2013)
Based on research that aims to describe and mengekspla-nasikan patterns political intervention in the judicial process Komando Jihad, and basing on non-doctrinal approach, it is known that the process of checking and passing judgment in the case Komandi Jihad, can not be separated from the executive power and the intervention or military, conducted through: (a) the use of military kekuatasan, which shall: (1) structural interventions, whether made directly or indirectly, (2) non-structural interventions, (b) through Intelligence Operating System, which is done through the strategy are: stocking, fishing rods and nets as well; glassware and mastered. Key word : Komando jihad, intervention, trial.